Study the ability of balance, length and mass of college students - Almojamay, Ahmed Sabea Atea; Tahseen, Tahseen Husni; Shehab, Mohamed Walid (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to identify the ability of balance, height, mass and level of differences for students of the College of Physical Education and Sports Sciences University of Baghdad and for all four stages. The importance of research in an analytical study is to know the level of this trait they have and at various stages is an evaluation study of this trait, and fit the view of researchers to be a project of evaluative studies based on the development of programs that help to develop this trait, the study included a sample of (201) students, after the exclusion of the retirees as well as athletes and players in clubs, the researchers used Mass measuring tool of the body containing a ruler for measuring height, in addition to the challenge-Disc (level 5), and used the statistical bag (SPSS) to extract results as the following: (Mean), (Std),(ANOVA), (L.S.D) showed the highest stability was for the fourth stage, the third stage, the first stage, and finally the second stage. They concluded that the advanced academic stages affect the student's acquisition of this ability and this may include the rest of the abilities. The results of the overall static balance of all stages showed a preference over dynamic balance, indicating that the dynamic balance is more difficult in its performance than the static balance